A software tool for simulating contaminant transport and remedial effectiveness in sediment environments. (November 2018) - Shen, Xiaolong; Lampert, David; Ogle, Stephen; Reible, Danny
Abstract: Sediments have often acted as sinks for contaminants that possess strong affinity for solids near historical pollution sources. Mathematical models describing the evolution of contaminant concentrations in sediment environments provide a scientific basis for decision support and remediation design. Herein, novel software (CapSim) is introduced including processes relevant to natural attenuation and in-situ treatment and containment (capping). The tool has been used as a basis for remedial design at a number of sites throughout the United States. CapSim is built on the concept of an arbitrary number of layers that each exhibit traditional porous media transport processes including sorption (linear and non-linear, transient or local equilibrium), advection, diffusion, dispersion, multicomponent linked reactions and, critically, processes specific to the sediment-water interface including bioturbation of both solids and porewater, deposition, consolidation, and interaction with the overlying surface water. A summary of recent applications and selected simulations of key features are presented. Highlights: A GUI software (CapSim) is developed to model the transport processes of multiple chemical species in a multi-layered sediment and capping system. The dynamic processes of the chemical species, such as reactions and the sorption/desorption between the porewater and solid particles are included. The typical diagenetic processes, including hyporheic exchange, bioturbation, deposition, oscillating groundwater flows are included.